2019
DOI: 10.3390/en12030461
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Transient Pressure Characteristics in a Helico-Axial Multiphase Pump

Abstract: In oil and gas exploitation, the multiphase pump is a vital piece of equipment to guarantee production with high efficiency and stable operation. The complicated pattern of multiphase flow in the multiphase pump affects the pump performance; for this reason, the multiphase performance and the inner flow should be sufficiently investigated. In the present work, a liquid-gas multiphase pump is designed and manufactured, and then tested in a specialized test rig to reveal the transient pressure characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Experimental flow loop of a gas-liquid two-phase three-stage pump: 1 air compressor, 2 gas buffer tank, 3 gas mass flowmeter, 4 plunger pump, 5 liquid mass flowmeter, 6 gas-liquid mixing section, 7 gas-liquid mixer, 8 experimental pump, 9 torque tachometer, 10 electric motor, 11 pneumatic control valve, 12 gas-liquid separator, 13 micropore muffler, 14 water tank, 15 backflow valve.…”
Section: Figurementioning
confidence: 99%
“…Experimental flow loop of a gas-liquid two-phase three-stage pump: 1 air compressor, 2 gas buffer tank, 3 gas mass flowmeter, 4 plunger pump, 5 liquid mass flowmeter, 6 gas-liquid mixing section, 7 gas-liquid mixer, 8 experimental pump, 9 torque tachometer, 10 electric motor, 11 pneumatic control valve, 12 gas-liquid separator, 13 micropore muffler, 14 water tank, 15 backflow valve.…”
Section: Figurementioning
confidence: 99%
“…A multiphase helico‐axial pump with an innovative structure and employing the splitter blades was provided by Xu et al 14 They observed that flow control is significant and challenging in the multiphase pump and requires more blades. The splitter blades aid the performance of the helico‐axial pump more than any other rotor‐dynamic pump as it helps in improving the control during the downstream flow, whereas eliminating the increase in exclusion coefficient at the impeller inlet.…”
Section: Types Of Multiphase Pumpsmentioning
confidence: 99%
“…[24] built an experiment facility that would allow visualization inside the impeller to study the gas-liquid flow patterns inside a centrifugal pump impeller, the effects of the gas-liquid flow pattern, bubble changes, and the flow in the impeller on the performance of the centrifugal pump were researched under different operating conditions. In addition, some related research was carried out on the multiphase pump with experimental methods, to obtain some valuable conclusions [25][26][27].…”
Section: Introductionmentioning
confidence: 99%